2021
DOI: 10.3389/fmicb.2021.675480
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Serum Metabolites and Fecal Microbiota Involved in Ewe Follicular Cyst

Abstract: While the interactions of the gut microbiome and blood metabolome have been widely studied in polycystic ovary disease in women, follicular cysts of ewes have been scarcely investigated using these methods. In this study, the fecal microbiome and serum metabolome were used to compare between ewes diagnosed with ovarian cystic follicles and ewes with normal follicles, to investigate alterations of the fecal bacterial community composition and metabolic parameters in relation to follicular cystogenesis. Ewes fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The gut microbiota, which refers to all microorganisms present in the gastrointestinal tract ( Kim et al, 2020 ), has important roles in the digestion ( Rowland et al, 2018 ), metabolism ( Nicholson et al, 2012 ), immunity ( Round & Mazmanian, 2009 ; Thaiss et al, 2016 ), and entro-endocrine function ( Rastelli, Cani & Knauf, 2019 ) of the host. However, in a state of dysbiosis, the gut microbiota can cause many diseases, such as diarrhea ( Wang et al, 2018 ; Xi et al, 2021 ), follicular cysts ( Feng et al, 2021 ), and bacterial pneumonia ( Zhao et al, 2021 ). Thus, the gut microbiota can affect the health of the host either positively or negatively.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota, which refers to all microorganisms present in the gastrointestinal tract ( Kim et al, 2020 ), has important roles in the digestion ( Rowland et al, 2018 ), metabolism ( Nicholson et al, 2012 ), immunity ( Round & Mazmanian, 2009 ; Thaiss et al, 2016 ), and entro-endocrine function ( Rastelli, Cani & Knauf, 2019 ) of the host. However, in a state of dysbiosis, the gut microbiota can cause many diseases, such as diarrhea ( Wang et al, 2018 ; Xi et al, 2021 ), follicular cysts ( Feng et al, 2021 ), and bacterial pneumonia ( Zhao et al, 2021 ). Thus, the gut microbiota can affect the health of the host either positively or negatively.…”
Section: Introductionmentioning
confidence: 99%
“…According to the group, distinguished clusters were shaped in the PLS-DA plot, indicating that the metabolic phenotype was dramatically changed by SAP-AKI and ZYD ( Figure 3(b) ). Correspondingly, permutation test showed a good interpretability and predictability of this PLS-DA model (R2Y 0.878, P = 0.01; Q2 0.531, P =0.01) ( Figure 3(c) ) [ 43 ]. Thus, the subsequent analysis could be implemented.…”
Section: Resultsmentioning
confidence: 96%
“…Totally, 814 metabolites were identified from the 21 serum samples. Unsupervised method PCA presented the variation trend in the data and detected the potential outlier of serum samples [ 43 ]. The PCA scatter plot ( Figure 3(a) ) showed that the first principal component (PC1) covered 14.59% of the variation and separated the SAP-AKI status and healthy control group (except one outlier in the MG).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, food compounds) and some of them are exclusive of bacterial origin with a key role in host-microbiota cross-talk . These metabolic changes driven by bacteria have been documented at fecal, urine, and serum levels. , Dietary interventions are emerging as a strategy to reshaping and modulate not only the gut microbiota composition, but even their metabolomes, with concomitant positive effects on the hosts . Similarly, it is demonstrated that the administration of exogenous beneficial bacteria in a close pre-existent ecosystem generates metabolic mutualistic benefits for both the microbial community and the host. , …”
Section: Discussionmentioning
confidence: 99%